If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-9=6x-18/2
We move all terms to the left:
3x-9-(6x-18/2)=0
We add all the numbers together, and all the variables
3x-(6x-9)-9=0
We get rid of parentheses
3x-6x+9-9=0
We add all the numbers together, and all the variables
-3x=0
x=0/-3
x=0
| x÷24=5÷12 | | 5y/6-1/3=-7/6 | | 5(6-2a)=100 | | 4(-4+x)-2x=-6-3x | | -8=-7(-4x+8)+8(x-3) | | 17=x÷3 | | Y+168+5x-48=180 | | 1/x-x-1/8=6 | | 2(×+4)-5=2x+3 | | 4(m-4)+7m=-93 | | 1/3(9x+27)-4=1/2(2×+54) | | x=1/4=2x=3/12=7/9 | | -3y-11=9y+13 | | 12x+7=3x+4 | | (7x^2-488)=0 | | -3y-11=9y+14 | | -30-a=-2(8+2a)-4a | | |x+2|=5-x | | 8(r+2=64 | | 9+3x+(2x-2)=67 | | (x-12)+x=-5 | | 6-6x=6(x+7) | | 5x-8=123 | | 20-6x=50-26x | | -6(x-3)-4(x-2)=-4 | | 1/4(a+10)=10 | | n=13÷-1 | | 13+2x-14=x | | (3x-11)+x=49 | | 3x+4=7(x+2)+2 | | 10+x=5(x+2) | | 6+1x=33-2x |